Efektivitas video dan leaflet dalam meningkatkan pengetahuan dan sikap tentang bahaya merokok pada remaja - Hariza Adnani; Lailatul Fadila; Siti Royani (STIKes Surya Global Yogyakarta, 2021)
The lack of evidence regarding two or more health education media designed together to help increase knowledge and change adolescent attitudes in decision-making to stop smoking. The purpose of this research is to determine the effectiveness of video media and leaflets in increasing the knowledge and attitudes of adolescents about the dangers of smoking. This research was a pre-experimental research with one group pretest posttest design. The population of the study was male adolescents at SMP 2 Pandak Bantul as many as 233 people with a sample of 70 people were calculated using the slovin formula. Technique sampling used purposive sampling method. Data analysis in this study used the paired sample t test. The results showed that there were differences between knowledge about the dangers of smoking in adolescents before and after being given video and leaflet media intervention with a significance value (p-value) = 0.002 0.05; there was a difference between attitudes about the dangers of smoking in adolescents before and after being given the intervention of video media and leaflets with a significance value (p-value) = 0.001, 0.05. The conclusion of this study was both video media and leaflets were effective in increasing adolescent’s knowledge and attitudes about smoking.